International trade promotion methods for SMEs in low and lower-middle-income economies - Smith, John Solunta (International Journal of Financial, Accounting, and Management, 2019)
Purpose: The study examines the determinants of SMEs international trade promotion in low and lower-middle-income economies. It also aims to further explain the participation or non- participation of SMEs in international trade promotion; recommended policies to increase SMEs' international trade promotion. Design/Research method: The author used the Gravity Theory in economics with mixed methods on the World Bank enterprises Survey dataset 2009 – 2018, using panel data regression models. Tests of multicollinearity using Stata entirely guided the models. The Pairwise correlation, the variance inflation factors, hausman test, testparm, and reverse causality test using the Poisson Pseudo Maximum Likelihood Model estimator were used. Findings: The results show that Small enterprises do not significantly promote international trade, while medium enterprises significantly do. The study finds rule of law, education, bank private credits, firms’ age, and trade openness as major determinants of SME trade promotion while inflation and tax constraints are somewhat determinants. The study found no evidence of reverse causality between exports and SMEs. Limitation: The study is limited in the coverage of the Key Informants Interviews (KII) used by the author to inform the discussion. The KII was only conducted in Liberia with SMEs engaged in exporting while the research data covered 56 low and lower-middle-income economies. Future expansion in the coverage of the KII is recommended. Implication: This study will be useful for policymakers who are engaged with the development of SMEs in low and lower-middle-income countries and academics in the fields of economics and international business management Keywords: Gravity model, SMEs, Trade promotion How to cite: Smith, John Solunta. (2019). International trade promotion methods for SMEs in low and lower-middle-income economies. International Journal of Financial Accounting and Management, 1(2), 105-118.